Biotechnological Perspectives of Omics and Genetic Engineering Methods in Alfalfa - Hrbáčková, Miroslava; Dvořák, Petr; Takáč, Tomáš; Tichá, Michaela; Luptovčiak, Ivan; Šamajová, Olga; Ovečka, Miroslav; Šamaj, Jozef (Frontiers in Plant Science, 2020)
For several decades, researchers are working to develop improved major crops with better adaptability and tolerance to environmental stresses. Forage legumes have been widely spread in the world due to their great ecological and economic values. Abiotic and biotic stresses are main factors limiting legume production, however, alfalfa (Medicago sativa L.) shows relatively high level of tolerance to drought and salt stress. Efforts focused on alfalfa improvements have led to the release of cultivars with new traits of agronomic importance such as high yield, better stress tolerance or forage quality. Alfalfa has very high nutritional value due to its efficient symbiotic association with nitrogen-fixing bacteria, while deep root system can help to prevent soil water loss in dry lands. The use of modern biotechnology tools is challenging in alfalfa since full genome, unlike to its close relative barrel medic (Medicago truncatula Gaertn.), was not released yet. Identification, isolation and improvement of genes for abiotic and/or biotic stress-tolerance significantly contributed to the progress of our understanding how crop plants cope with these environmental challenges. In this review, we provide an overview of the progress that has been made in high-throughput sequencing, characterization of genes for abiotic or biotic stress tolerance, gene editing, as well as proteomic and transcriptomic techniques bearing biotechnological potential for alfalfa improvement.